Intergroup Emotions, Perceived Threats and Hostility against Foreigners: Comparing Brazil, Portugal, and Spain - Gondim, Sônia Maria G. (2018)
This study analyzed whether hostility towards foreigners perceived as competitors in the labor market would be related to the perception of threat (symbolic and economic) and negative intergroup emotions. 270 people between 18 and 63 years participated. In Brazil (N = 89), mostly men (59%) and average age 32.5 years; In Portugal (N = 87), mostly men (56.3%) and average age 39.9 years; in Spain (N = 94), mostly women (53.2%) and average age of 32.8 years. The results (t-test, analysis of variance and multiple regressions) indicated that in Spain negative emotions are associated with less hostility towards immigrants; In Brazil, positive emotions are associated with hostile attitudes. In Portugal, the relationship between positive emotions and hostility is positive, but not signifi cant. The symbolic threat was the best predictor of hostility only in the Brazilian sample. Positive emotions predispose to a greater kindness towards foreigners in the three countries. The main conclusion of the study is that the economic crisis does not seem to be associated with the perception of competitiveness of foreigners in the local labor market and hostility towards this social group.